Home office ou lar-ateliê?: novas configurações de ambiente de trabalho para profissionais da indústria criativa - Heineck, Amanda Corbellini (Universidade do Vale do Rio dos Sinos, 2021)
Home offices are structured work spaces in the homes of several professionals, but, according to a conception pre-established in the popular imagination, the configuration of these spaces basically presents a table, a chair and a computer, where the professional develops his work activities. With another look, this study promotes the deconstruction of this dominant thought, seeking a new concept of home office for professionals in the creative industry. The work begins with a bibliographic review on themes that involve the concept of home office, from which seeks to expand knowledge about this type of work in a residential environment. Massimo Canevacci's proposal, presented in his study The Polyphonic City: an essay on the anthropology of urban communication, is used as a guiding method of the research. The methodology of the work follows three stages: the first focuses on the mapping of professionals who work in the home office, presenting a final selection of ten professions analyzed; the second consists of observing the chosen contexts, with the analysis and interpretation of the data, in which the home office spaces are understood as fragments of the study; and, finally, the third stage is characterized by the proposal of design guidelines derived from the information collected in the previous stages. Still in this stage, a phase of project experimentation is carried out, in which one seeks to apply the knowledge generated in the conception of a new concept for the home office, which turns out to be the home-studio. From this conception, a visual representation of models of environments is developed for the selected professionals. The findings achieved, associated with the knowledge acquired in the study, enabled the verification of several variables and possible configurations of residential work spaces.
Keywords: Home office; Desconstrução; Indústria Criativa; Reconfiguração; Lar-ateliê; Deconstruction; Creative Industry; Reconfiguration; Home-atelie; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo